EVALUASI DAMPAK PROGRAM KOTAKU (KOTA TANPA KUMUH) DALAM MENGURANGI PERMUKIMAN KUMUH DI KELURAHAN BANGETAYU KULON DAN KELURAHAN BANJARDOWO KECAMATAN GENUK KOTA SEMARANG - Sarah Dewi, Widya (Journal of Public Policy and Management Review, 2025)
Based on Law No. 1 of 2011 concerning Housing and Residential Areas (PKP), slums are uninhabitable settlements characterized by irregular buildings, high building density, and substandard building quality and facilities and infrastructure. Based on Semarang Mayor Regulation Number 19 of 2023 concerning the Plan for Prevention and Improvement of the Quality of Slum Housing and Slum Settlements in 2022-2026, the Government has a target for Semarang City with 0% or zero slum areas. The problem of slums is not a new problem but has become a classic problem phenomenon both at the global, regional, national and local levels. The evaluation of the KOTAKU program in this study aims to measure the success of the KOTAKU program in reducing slums and achieving the target of a City Without Slums. By conducting periodic evaluations, it can monitor the development of slum conditions and ensure that the arrangement program is running according to the set targets. The aim of this research is to evaluate the output of the City Without Slums Program (KOTAKU) in Genuk District and evaluate the outcomes of the City Without Slums Program (KOTAKU) in Genuk District. The research method used in this research is descriptive qualitative with data collection techniques through interviews and literature study. The theory used in this research is research by Hariani (2017) and Diana, et al (2022) regarding Evaluation of Output and Outcomes. The results of this research show that the KOTAKU Program has succeeded in increasing public access to information, the program coverage is quite broad, and the frequency of effective implementation. Apart from that, this program has also met community needs in terms of building and improving access to proper infrastructure, increasing community knowledge and skills in terms of understanding and managing the environment better, such as how to care for public facilities that have been built or repaired and maintaining infrastructure. However, based on this, there are still several challenges that need to be overcome, such as budget limitations, uncertain implementation schedules, and the existence of segments of society that are less concerned about program sustainability.